Ralph Greenson's Child Analytic Understanding and Technique: A Heuristic Examination. Issue 1 (31st December 2022) - Sugarman, Alan
ABSTRACT: Despite Ralph Greenson not being a child analyst, his two papers on the analysis of a gender-disordered boy offer a heuristic opportunity to consider current controversies in child analysis. Thus, his material is examined in terms of current considerations about how to understand and work with such disturbances, the distinctions between being a developmental object and providing a corrective emotional experience, the role and place of play in clinical technique, the analyst's role as a real object, and the importance of promoting a sense of self-agency in child analysis. Greenson's relatively sophisticated dynamic formulation of the boy's gender issues is contrasted with his unidimensional technical approach with its deemphasis of insight into and articulation of the boy's internal/subjective world. This approach limited the boy's opportunity to achieve insightfulness and to terminate analysis with a sense of self-agency. It also could have left him vulnerable to later depression during adolescence because he never realized or mastered the complex emotions, conflicts, and relationship with his parents that contributed to his wishes to be and act like a girl. Instead, he altered his behavior to comply with his analyst's wish that he act in a stereotypically masculine way.